The Solar Shading Performance of the Multi-Angled Façade System and Its Impact on the Sustainable Improvement of the Buildings - Loay Hannoudi; Noha Saleeb; George Dafoulas (Energies)
This research paper explores the visual potential of the multi-angled façade system, allowing office employees to achieve optimal exposure to the external environment through the room façade. This contributes to sustainability objectives by enhancing indoor climate quality, promoting health and well-being, and aligning with the UN Sustainable Development Goals 3, 9, and 11. This façade concept provides a solution to the issue of shading devices being fully closed for long periods due to intense solar radiation on the room’s window. The concept of a multi-angled window involves incorporating two differently oriented window sections within each façade along a vertical axis (right and left), rather than tilting them upward or downward. The larger section is oriented more toward the north to maximize daylight access and external views, while the smaller section faces south to enhance passive solar heating. The visual potential is assessed based on the periods when the solar shading devices are not fully closed—meaning one section of the multi-angled façade may remain open while the other is shaded. To evaluate this, along with the resulting energy consumption and indoor climate, the software program IDA ICE version 4.8 is utilized. Simulation results indicate that the duration of complete shading closure is significantly lower for a multi-angled façade compared to a flat façade, in some instances nearly half, thereby improving visual comfort, daylight availability, and heat gain while simultaneously reducing spatial energy consumption.